Financial Socialization of Fintech Behavior Adaptation Through Financial Literacy in Small Businesses - Ulima, Citra; Alfiana, Alfiana; Iswari, Hanif Rani (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
The acceleration of financial technology (fintech) triggers a gap in adaptation behavior between digital inclusion and real financial management performance in the small business sector. This study aims to analyze the influence of financial socialization on fintech behavior adoption through financial literacy in small businesses in Sawojajar Village, Malang City. This study uses a quantitative approach with an explanatory design. Primary data was collected through a five-level Likert scale questionnaire to small business owners or managers who have used financial technology platforms, such as QRIS and digital capital financing instruments. Data analysis was carried out using Structural Equation Modeling based on Partial Least Square (PLS-SEM) with the help of SmartPLS, through the evaluation of measurement models and structural models as well as testing for direct and indirect influences. The results of the study showed that financial socialization had a positive and significant effect on financial literacy with a coefficient value of 0.482 and a T-statistic of 6.112. Financial socialization and financial literacy also have a positive and significant effect on fintech behavior adoption with coefficients of 0.359 and 0.534, respectively. In addition, financial literacy was proven to play a role as a mediating variable with an indirect effect of 0.257 and a T-statistic of 3.618. These findings show that strengthening financial literacy through financial socialization can encourage the adoption of financial technology that is more productive, safe, and sustainable in small businesses.